Azithromycin Attenuates Lung Inflammation in a Mouse Model of Ventilator-Associated Pneumonia by Multidrug-Resistant Acinetobacter baumannii - Yamada, Koichi (American Society for Microbiology, 2013)
Acinetobacter baumannii is one of the main pathogens that cause ventilator-associated pneumonia (VAP) and is associated with a high rate of mortality. Little is known about the efficacy of macrolides against A. baumannii. In order to confirm the efficacy of azithromycin (AZM) against VAP caused by multidrug-resistant A. baumannii (MDRAB), we used a mouse model that mimics VAP by placement of a plastic tube in the bronchus. AZM (10 and 100 mg/kg of body weight) was administered subcutaneously every 24 h beginning at 3 h after inoculation. Phosphate-buffered saline was administered as the control. Survival was evaluated over 7 days. At 48 h postinfection, mice were sacrificed and the numbers of viable bacteria in lungs and bronchoalveolar lavage fluid were compared. Histopathological analysis of lung specimens was also performed. The treatment groups displayed significantly longer survival than the control group (P < 0.05). AZM did not have an antimicrobial effect. Histopathological examination of lung specimens indicated that the progression of lung inflammation was prevented in the AZM-treated groups. Furthermore, total cell and neutrophil counts, as well as cytokine levels, in bronchoalveolar lavage fluid were significantly decreased (P < 0.05) in the AZM-treated groups. AZM may have a role for the treatment of VAP with MDRAB because of its anti-inflammatory effects.